Antara Matrilineal dan Faraidh: Negosiasi Otoritas dan Pergeseran Pola Penyelesaian Sengketa Waris di Minangkabau (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines the dynamic tension between Minangkabau matrilineal customary law and Islamic inheritance law (faraidh) in resolving inheritance disputes, with Nagari Alahan Panjang, Lembah Gumanti District, Solok Regency as the case study. Employing a qualitative field research approach within a legal pluralism framework (Griffiths, 1986; Hooker, 1975), data were gathered through in-depth interviews with ninik mamak, religious figures, the nagari leader, and community members directly involved in disputes, conducted in February 2026. The findings reveal three forms of inheritance disputes reflecting escalating severity: misappropriation of pusaka property by mamak figures, unauthorized transfer of communal ulayat land triggering mass protests in 2023, and disputes escalating into criminal acts, notably an arson case. The findings further document a shift in dispute resolution patterns: while customary mechanisms through the bajanjang naik batanggo turun principle remain effective in approximately 70% of cases, escalating economic pressures and generational divergence in understanding faraidh are increasingly bypassing traditional mediation and forcing disputes into the criminal justice system. Both systems share substantive convergence in prioritizing deliberation (musyawarah), justice, and social harmony, reflected in the philosophical principle of adat basandi syarak, syarak basandi Kitabullah. Contributing to legal pluralism scholarship, this study empirically identifies the structural conditions under which integration of both systems succeeds or fails: effective dispute resolution requires the simultaneous involvement of ninik mamak and ulama from the earliest stage of conflict, supported by written documentation of deliberation outcomes and improved inheritance law literacy in the community.